Design of Slip Ring Based on SSP Compensation and Variable Frequency Control - FENG Xin, FU Zhuang, WANG Kejin, HAO Gaofeng (Shanghai Jiaotong Daxue xuebao, 2021)
In order to avoid the disadvantages of the traditional slip ring, such as easy wear and easy accumulation of static electricity, a novel slip ring design method based on series series parallel (SSP) compensation and variable frequency control is proposed. First, the magnetic circuit of the non-contact slip ring is modeled. The leakage inductance and the magnetizing inductance of the loosely coupled transformer, namely the primary side series compensation and secondary side series parallel compensation, are compensated respectively. Next, due to the influence of temperature and other factors, the sensitivity of some components is analyzed, and the relationship between component parameter variation and resonance frequency variation is obtained. After that, a phase difference detection method based on Hanning window fast Fourier transform is proposed, which can avoid the restriction of hardware performance and improve the anti-interference ability. Finally, according to the calculated phase difference and critical quality factor, a variable frequency control method based on zero phase angle is proposed to help the system work at zero phase angle, thereby reducing the loss of reactive power. The simulation results show that when the component parameters change, the proposed method based on SSP compensation and variable frequency control can quickly help the system work in zero phase angle state, and then improve the efficiency of the system. A prototype is designed to verify the proposed method, and the experimental results are basically consistent with the simulation results. Compared with no compensation method, the efficiency of the proposed method is increased by 5%. The research results show that the method proposed has a high robustness.